THE ANALYSIS OF FORMAL LINK IN WESTLIFE’S SONG - Sijono Sijono; Thomas Joni Verawanto Aristo (STKIP Persada Khatulistiwa Sintang, 2018)
Formal is formal links referring to the fact inside the language, that consist of verb form, parallelism, ellipsis, referring expression, conjunction, substitution, and repetition. This study uses descriptive qualitative research in which the researcher just describe the result of the implementation from the instruments and the data is obtained from articles, literary works, field notes, and personal documents in the form of words or pictures rather than numbers. The object of this study is formal links and the subject is Westlife’s songs. The analysis is taken from twelve songs of Westlife in their “Back Home” album. From the whole data the researcher found that most of songs consist of more than one formal link. The formal links are; Verb Form, Referring Expression, Repetition, Parallelism, Conjunction, and Substitution. From those formal links the most used in Westlife’s songs is Referring Expression, it can be seen that referring expression dominate the others links in eight songs from twelve songs. The songs that are dominated by referring expression are Us Against the World, Something Right, I’m Already There, When I’m With You, Have You Ever, It’s You, Catch My Breath and the Easy Way. From the result of analysis it can be concluded that Westlife’s songs has deep meaning which always referring with other words or elements and they avoid to repeat the identity of what they are sharing about again and again. To referring the meaning that they posted in their song’s lyric they used the third person pronouns like he, she, we, our, it, his, her, them. For the suggestion, the researcher recommends to the next researchers to analyze another part of discourse analysis such as discourse structure, discourse as dialogue, knowledge on discourse, etc.Keyword: Formal Link, Song Lyric, Weslife’s Song